2009
DOI: 10.1158/1078-0432.ccr-08-1276
|View full text |Cite
|
Sign up to set email alerts
|

Cdc7 Kinase Is a Predictor of Survival and a Novel Therapeutic Target in Epithelial Ovarian Carcinoma

Abstract: Purpose: There is a lack of prognostic and predictive biomarkers in epithelial ovarian carcinoma, and the targeting of oncogenic signaling pathways has had limited impact on patient survival in this highly heterogeneous disease. The origin licensing machinery, which renders chromosomes competent for DNA replication, acts as a convergence point for upstream signaling pathways. We tested the hypothesis that Cdc7 kinase, a core component of the licensing machinery, is predictive of clinical outcome and may consti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…The disappointing intent-to-treat analyses of large, conventionally designed trials, such as TACT and tAnGo, suggests that further improvements in adjuvant treatment will require individualized therapeutic decisions [116,117]. Cell cycle phase analysis of breast and ovarian cancers has shown that it is tumours displaying the accelerated cell cycle phenotype that are most likely to show a clinically relevant response to S-or M-phase-directed agents (Table 1, Figure 3B) [3,74,110,111,118]. As non-proliferating cells are radiation-resistant, whereas cycling cells are most sensitive to radiation insult during transit through G 2 and M phase, tumours displaying the accelerated cell cycle phenotype may also represent those that are most radiation-sensitive.…”
Section: Cell Cycle Phase Analysis As a Predictor Of Therapeutic Respmentioning
confidence: 99%
See 2 more Smart Citations
“…The disappointing intent-to-treat analyses of large, conventionally designed trials, such as TACT and tAnGo, suggests that further improvements in adjuvant treatment will require individualized therapeutic decisions [116,117]. Cell cycle phase analysis of breast and ovarian cancers has shown that it is tumours displaying the accelerated cell cycle phenotype that are most likely to show a clinically relevant response to S-or M-phase-directed agents (Table 1, Figure 3B) [3,74,110,111,118]. As non-proliferating cells are radiation-resistant, whereas cycling cells are most sensitive to radiation insult during transit through G 2 and M phase, tumours displaying the accelerated cell cycle phenotype may also represent those that are most radiation-sensitive.…”
Section: Cell Cycle Phase Analysis As a Predictor Of Therapeutic Respmentioning
confidence: 99%
“…This would translate into low therapeutic indices often found for conventional chemotherapeutic drugs targeting the cell cycle. However, potent cancer cell-specific killing has been demonstrated in preclinical models after inhibition of origin licensing [125] or, alternatively, origin activation through targeting Cdc7 kinase [111,118,126,127]. Tumour cell specificity is thought to result from transformed cells entering S phase with inadequate numbers of competent origins to complete chromosomal replication.…”
Section: The Dna Replication Initiation Machinery-a Promising Anti-camentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of Cdc7 in ovarian cancer correlates with tumor anaplasia, aneuploidy, and advanced clinical stage. The greatest discriminatory effect of Cdc7 expression was observed for stage 3 and 4 ovarian tumors, which make up the vast majority of epithelial ovarian carcinoma cases (35). Cdc7 and Dbf4 are overexpressed in malignant melanoma compared with benign melanocytic nevi, and Dbf4 overexpression has been associated with lower relapse-free survival (36,37).…”
Section: Cell Division Cycle 7 Overexpressionmentioning
confidence: 99%
“…Overexpression of Cdc7-ASK occurs in various types of cancer (Hess et al 1998;Nambiar et al 2007;Bonte et al 2008;Clarke et al 2009;Kulkarni et al 2009) and often correlates with poor prognosis, suggesting that deregulated Cdc7 kinase activity may promote survival of cancer cells and tumor progression. Recently, some small molecule inhibitors of Cdc7 kinase activity have been developed and are being tested in clinical trials as candidate anti-cancer drugs (Ito et al 2008;Montagnoli et al 2008;Vanotti et al 2008;Ermoli et al 2009).…”
mentioning
confidence: 99%